Nitrogen addition and drought impose divergent effects on belowground bud banks of grassland community: a meta-analysis - Wu, Jing; Hou, Xian-zhang; Zhu, Jin-lei; Miao, Ren-hui; Adomako, Michael Opoku (Frontiers in Plant Science, 2025)
Belowground bud banks (or bud-bearing organs) underlie grassland regeneration and community succession following ecosystem perturbations. Disturbances of nitrogen (N) enrichment, overgrazing, wildfire, and drought substantially affect grassland ecosystem succession and aboveground productivity. To understand the magnitude and direction of the disturbances on the belowground bud banks, we conducted a meta-analysis on 46 peerreviewed studies published from 1980 to 2023. The meta-analysis comprises 231 observations of bud bank density per unit area and 410 observations of bud bank density per tiller. Results indicate that N addition remarkably promotes bud banks densities and plant functional groups of grass in the belowground bud banks. While drought negatively affects bud banks densities and functional groups of grasses and forbs. We found that effects of the N addition and drought on the bud banks depend on the bud type, e.g., root sprouting buds, bulb buds, and dormant buds. However, grazing and wildfire have no significant effect on the bud banks. Our results suggest that the N addition and drought may significantly exert promotional and inhibitory effects, respectively, on belowground bud banks, critically altering plant regrowth, community succession, and grassland community dynamics.